The effect of angle of attack on the aeroacoustic environment within the weapons bay of a generic UCAV - Bacci, David; Saddington, Alistair J.; Bray, Derek (Elsevier, 2019)
Cavity flow studies are generally concerned with observing the effect of geometry changes whilst maintaining a fixed zero angle of attack. Cavities employed as weapons bays will, however, experience a range of angles of attack. This paper presents the first known results showing the effect of flight angle of attack on the aeroacoustic characteristics of an internal weapons bay installed in an uninhabited combat air vehicle (UCAV). The UCAV geometry consisted of a Boeing M219-type cavity in a Boeing UCAV1303 airframe. Numerical simulation was conducted using a full-scale detached eddy simulation model and representative transonic flight conditions. As well as the reference case of zero degrees, data for angles of attack of 3.0, 4.5 and 6.0 degrees were analysed. Experimental data was used to validate the reference computational model, which agreed with the overall fluctuating sound pressure level (OAFPL) to within the experimental uncertainty of 4 dB. Data from the computational model was post-processed with frequency-domain and time-frequency-domain techniques showing that the flow structure within the weapons bay was altered significantly by the angle of attack changes, affecting the mean pressure distribution, frequency spectra and resonant modes. Overall, increasing the angle of attack from 0.0 to 3.0 degrees produced an increment in the acoustic load whilst a further increase tended to affect the resonance mechanism and thereby reduce the coherence and the temporal footprints of the resonant modes.
Keywords: UCAV; Cavity; Aeroacoustic; Transonic